The N-end rule is mediated by the UBC2(RAD6) ubiquitin-conjugating enzyme. - Dohmen, R J (1991)
The N-end rule relates the in vivo half-life of a protein to the identity of its amino-terminal residue. Distinct versions of the N-end rule operate in all organisms examined, from mammals to bacteria. We show that UBC2(RAD6), one of at least seven ubiquitin-conjugating enzymes in the yeast Saccharomyces cerevisiae, is essential for multiubiquitination and degradation of the N-end rule substrates. We also show that UBC2 is physically associated with UBR1, the recognition component of the N-end rule pathway. These results indicate that some of the UBC2 functions, which include DNA repair, induced mutagenesis, sporulation, and regulation of retrotransposition, are mediated by protein degradation via the N-end rule pathway.